PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN CUSTOMER GEN Z PADA COFFE SHOP POINT COFFE BANDAR LAMPUNG - Abdillah, Satria Yuda; Ruslaini; Sutopo, Heri (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study aims to analyze the effect of service quality on Generation Z customer satisfaction at Point Coffee in Bandar Lampung. The research employs a quantitative method with data collection through online questionnaires distributed to 100 respondents, targeting Generation Z population who have experienced Point Coffee services, using purposive sampling technique. The findings indicate that service quality has a positive and significant impact on Point Coffee customer satisfaction, as evidenced by t-count value of 9.560 > t-table 1.984 and significance of 0.000 < 0.05. The relationship between variables is classified as strong with a correlation coefficient of 0.695, where service quality contributes 48.3% to customer satisfaction. This research provides important implications for developing coffee shop service strategies in addressing Generation Z consumer preferences